1948
DOI: 10.1172/jci101960
|View full text |Cite
|
Sign up to set email alerts
|

The Complement Content of Human Sera With Especial Reference to Malaria 1

Abstract: Our interest in the complement content of sera from healthy and diseased individuals was initiated by chance observations on the cephalincholesterol flocculation test (1). 'In our first performance of the test we inadvertently included several sera which had been inactivated and stored in the refrigerator over-night. All of these gave positive readings at 24 hours. Repetition of these tests, using sera from the same individuals, but fresh samples which were less than four hours old, yielded some negative and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This clinical association is well recognized in Africa (Graham et al, 2000;Bronzan et al, 2007). Hypocomplementemia, a marked decrease of serum complement components, is often observed in children and adults with acute malaria (Dulaney, 1947;Siddique and Ahmed, 1995). Hypocomplementemia in African patients with malaria may therefore increase susceptibility to S. Typhimurium, giving rise to co-infection with malaria and Salmonella.…”
Section: Discussionmentioning
confidence: 98%
“…This clinical association is well recognized in Africa (Graham et al, 2000;Bronzan et al, 2007). Hypocomplementemia, a marked decrease of serum complement components, is often observed in children and adults with acute malaria (Dulaney, 1947;Siddique and Ahmed, 1995). Hypocomplementemia in African patients with malaria may therefore increase susceptibility to S. Typhimurium, giving rise to co-infection with malaria and Salmonella.…”
Section: Discussionmentioning
confidence: 98%
“…As long ago as 1922, Radosavljevic concluded from semiquantitative tests then available that serum C' activity was reduced during the paroxysm in human malaria (4). In 1948 with the use of quantitative assays for C', Dulaney reported a general association of reduced C' in patients with malaria (5). More recent studies in heavily infected monkeys have found a striking depletion of C' shortly before death (6), and variation in C' and C' components levels during schizogony (7).…”
Section: Introductionmentioning
confidence: 99%
“…The high serum complement levels observed in obstructive jaundice were also found by Dulaney (1948), by Jordan (1953) and by Mandel and Lange (1955). Fischel (1953) and Boltax and Fischel (1956) described raised serum complement levels in tissue destruction.…”
Section: Inhibitors 01 Serum Complementmentioning
confidence: 84%